Poor prey quality is compensated by higher provisioning effort in passerine birds - Sarah Senécal (Nature Portfolio, 2021)
Abstract In altricial avian species, nutrition can significantly impact nestling fitness by increasing their survival and recruitment chances after fledging. Therefore, the effort invested by parents towards provisioning nestlings is crucial and represents a critical link between habitat resources and reproductive success. Recent studies suggest that the provisioning rate has little or no effect on the nestling growth rate. However, these studies do not consider prey quality, which may force breeding pairs to adjust provisioning rates to account for variation in prey nutritional value. In this 8-year study using black-capped (Poecile atricapillus) and boreal (Poecile hudsonicus) chickadees, we hypothesized that provisioning rates would negatively correlate with prey quality (i.e., energy content) across years if parents adjust their effort to maintain nestling growth rates. The mean daily growth rate was consistent across years in both species. However, prey energy content differed among years, and our results showed that parents brought more food to the nest and fed at a higher rate in years of low prey quality. This compensatory effect likely explains the lack of relationship between provisioning rate and growth rate reported in this and other studies. Therefore, our data support the hypothesis that parents increase provisioning efforts to compensate for poor prey quality and maintain offspring growth rates.